HISTORY OF DEVELOPMENT AND CURRENT TRENDS INDIVIDUALIZATION OF TEACHING IN PEDAGOGICAL THOUGHTS OF THE PAST AND THE PRESENT - Melikova, S.O. (Pedagogy of Higher and Secondary Education, 2002)
The article deals with the history of individual approach in training and present-day state of given problem.